Eksistensi Ahmadiyah di Kota Padang Pasca Peraturan Gubernur Tahun 2011 - Resti Febi Ramadani; Herwandi Herwandi; Lindayanti Lindayanti (Universitas Muhammadiyah Tapanuli Selatan, 2019)
This study seeks to find out how the existence of an organization, that is prohibited by the Indonesian government itself. This research uses historical research methods, including, heurustics, this activity collects the source of the object concerned such as books, archives, and megazine. Then source criticism, wich is sorting out the sources that have been collected, then interpretations, and historiography. Drawing conclusions using a descriptive-analytical approach. This study found that Ahmadiyya in West Sumatera, which in 2005 and 2011 the government had banned this organization, through governors regulations and as well as getting resistance from the community, howefer it seems that the Ahmadiyya still exists until now, even having a good relationship with the non-Ahmadiyya community.Keywords: Existence, Ahmadiyya, Padang